Human cloning as reproductive means in future: a qualitative thematic study of underpinning values - Castelyn, Camille; Van Staden, Werdie; Pepper, Michael S. (Frontiers in Public Health, 2024)
Background and objective: The possibility of using human cloning to reproduce has been met with unease, shock, and prohibition in many countries, as well as the International Committee for Monitoring Assisted Reproductive Technology and the World Health Organisation. Exploring the value judgments that underpin these and other responses to reproductive human cloning (RHC) was the objective of this study. Methods. In a qualitative design, this study explored values in their variety underpinning responses to RHC by conducting individual semi-structured in-depth interviews among nine scholars who were purposively sampled for contributing various perspectives. Thematic analysis was used to uncover qualitative contents systematically. Results: Regulation of RHC, the first theme, was valued highly but this should become more sophisticated than plain prohibition and draw on accountable societal engagement that is well-informed by current knowledge and further research, rather than be misled by for example the mistaken assumption that cloned offspring would be exact replicas. The second theme was about potential consequences of RHC for which engagement and regulations should account. It concerns the valuing of the personhood and dignity of offspring from RHC, and averting exploitation and potential unwanted societal consequences. In the third theme, participants valued the individual's freedom to choose and reproduce. Conclusion: Recognising the needs among people who cannot reproduce in other ways, the agenda for the societal engagement on RHC suggested by this study is extensive and challenging. It includes that potential consequences should be pre-empted, exploitation of RHC be averted, criteria of acceptability and non-acceptability of using RHC be developed, and the limits to the use of RHC be articulated in accordance with technological constraints and the values, resources and preparedness of societies.